The effect of distiller's grains on the prevalence and concentration of Escherichia coli O157 in cattle - Jacob, Megan E. (Kansas State University, 2010)
Escherichia coli O157 is a major foodborne pathogen that causes enteritis in humans ranging in severity from mild to bloody diarrhea to hemolytic uremic syndrome and even death. Cattle are asymptomatic carriers and fecal shedding of the organism is the major source of contamination of food and water for human infections. Distiller’s grains (DG) are ethanol fermentation co-products that are valuable feed ingredients for use in cattle diets. Previous research suggests an association between feeding DG and an increased fecal shedding of Escherichia coli O157:H7. The objectives of the research were to evaluate fecal E. coli O157:H7 prevalence and concentration in cattle fed diets with and without DG, determine if the association was dependent on inclusion level or form (wet or dried), evaluate the association in populations of cattle at harvest, and evaluate a potential intervention strategy. Our results indicated that cattle fed DG had a higher prevalence and shed a higher concentration of E. coli O157 than cattle fed diets without DG. The relationship was not dependent on the DG form, however, it was affected by the inclusion level of DG in the diet. Cattle that were fed 40% DG had a higher E. coli O157:H7 prevalence than cattle fed control or 20% DG diets and cattle fed 20% DG had a prevalence that was not statistically different from control cattle. The same response was observed in a subpopulation of cattle, termed super-shedders, which shed E. coli O157:H7 at higher concentrations than the general population. At harvest, we did not find differences in E. coli O157:H7 or super-shedder prevalence between cattle fed diets with or without DG, however, study design limitations affected the power of the study. Finally, previous work had shown that cattle fed dry-rolled grains had a decreased prevalence of E. coli O157:H7 when compared to cattle fed steam-flaked grains. We evaluated the effect of feeding DG and dry-rolled corn (DRC), alone or in combination, and observed no difference in E. coli O157 prevalence between cattle fed either DG or DRC diets. In conclusion, DG supplementation increased the prevalence and concentration of E. coli O157:H7 in cattle.
Keywords: Escherichia coli O157; cattle; distiller's grains; food safety; Biology, Microbiology (0410)